Habitat for Humanity and the Support of Civic Participation (In Factis Pax: Journal of Peace Education and Social Justice, 2011)
What is the best way for individuals to develop skills for civic participation? Too often civic participation skills are described and/or memorized without real understanding. The Integrative Ethical Education model is a comprehensive approach to ethical education that focuses on skill development within context. It uses a novice-to-expert approach to developing the kind of ethical skills that any successful ethical agent must have available for moral action. We describe the model briefly and then use this model to assess Habitat for Humanity’s systematic attempt to bring disenfranchised members of society into the community as full participating members. We also address the areas in which further work can be done to assist Habitat in achieving greater success as an agent of civic change.